Green Economy: Bibliometric Analysis Approach - Alsmadi, Ayman Abdalmajeed; Alzoubi, Marwan (International Journal of Energy Economics and Policy, 2022)
With the increased efforts and focus on sustainable development and changes in the climate, literature has given more attention to the green economy. However, researchers have not yet been totally able to consensus on the definition of this phenomenon. The study presented in the paper provides an overview of the advancements present in research on the green economy for the period from 1990 to 2020. Using a bibliometric analysis approach, the paper summarizes the trends of development and the status quo of the green economy. The aim is to provide the reader with guidance and a solid conceptual framework for future research.